2000
DOI: 10.1111/j.1745-6584.2000.tb00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems Associated with Estimating Ground Water Discharge and Recharge from Stream‐Discharge Records

Abstract: Ground water discharge and recharge frequently have been estimated with hydrograph‐separation techniques, but the critical assumptions of the techniques have not been investigated. The critical assumptions are that the hydraulic characteristics of the contributing aquifer (recession index) can be estimated from stream‐discharge records; that periods of exclusively ground water discharge can be reliably identified; and that stream‐discharge peaks approximate the magnitude and timing of recharge events. The firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 24 publications
1
100
0
7
Order By: Relevance
“…Hydrograph separation is based on the assumptions that stream discharge can be directly correlated to groundwater recharge. Several factors are neglected in this approach, such as evapotranspiration and bank storage, leading to considerable uncertainties (Halford and Mayer, 2000). Tracer-based hydrograph separation further assumes that preevent water and event water are clearly different in isotopic or chemical composition and that the composition is constant in space and time; both being conditions that are often not met (Genereux and Hopper, 1998).…”
Section: Considerations For Choosing Appropriate Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrograph separation is based on the assumptions that stream discharge can be directly correlated to groundwater recharge. Several factors are neglected in this approach, such as evapotranspiration and bank storage, leading to considerable uncertainties (Halford and Mayer, 2000). Tracer-based hydrograph separation further assumes that preevent water and event water are clearly different in isotopic or chemical composition and that the composition is constant in space and time; both being conditions that are often not met (Genereux and Hopper, 1998).…”
Section: Considerations For Choosing Appropriate Methodsmentioning
confidence: 99%
“…Furthermore, in cases where drainage from bank storage, lakes or wetlands, soils, or snowpacks contributes to stream discharge, the assumption that baseflow discharge represents groundwater discharge may not hold (Halford and Mayer, 2000). The limited number of stream gauging stations constrains the resolution of this method.…”
Section: Hydrograph Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…The reviews of Hall (1968), Smakhtin (2001) and Schwartz (2007) provide a history of methods for baseflow separation, and discuss the problems related to the definition of baseflow, as well as the underlying assumptions of the different separation methods. In the context of identifying groundwater recharge from streamflow records, the underlying assumptions that underpin many methods were examined by Halford and Mayer (2000). They concluded that identifying the groundwater contribution from streamflow records can be ambiguous due to drainage exponentially decreasing from other sources, such as bank storage, wetlands and the unsaturated zone.…”
Section: Introductionmentioning
confidence: 99%
“…More often streamflow recession analysis methods are adjusted for a specific case of application or a distinct set of catchments. However, when storage-outflow behavior is solely analyzed with streamflow data, multiple-methods approaches have been suggested to overcome potential biases of a single recession analysis method (Halford and Mayer, 2000).…”
Section: Introductionmentioning
confidence: 99%